Post-traumatic Stress Disorder and Associated Factors 1 Year After the Beginning of the COVID-19 Pandemic Among Chinese Residents - Shen, Xin; Yan, Shijiao; Jiang, Heng; Cao, Hui; Dowling, Rowan; Feng, Jing; Lei, Zihui; Li, Crystal Jingru; Han, Xiaotong; Lv, Chuanzhu; Gan, Yong (Frontiers in Psychiatry, 2021)
Background: By investigating the incidence of post-traumatic stress disorder (PTSD) among residents during a period of low transmission, this study reflects the long-term impact of coronavirus disease 2019 (COVID-19) and identify which categories of residents are more likely to develop PTSD due to an acute infectious disease crisis, facilitating the development of targeted strategies to protect mental health after outbreaks of similar acute infectious diseases in the future. Methods: A cross-sectional survey was conducted in China from 4 to 26 February 2021. A convenience sampling strategy was adopted to recruit participants. Participants were asked to complete the PTSD Checklist for DSM-5 (PCL-5). A multivariable linear stepwise regression analysis model was used to identify which factors were associated with PTSD in residents of China. Results: A total of 2,361 Chinese residents completed the questionnaire. The mean PCL-5 score for the respondents was 13.65 (SD=8.66), with 219 (9.28%) patients having probable PTSD symptoms. Respondents who were female (β= 0.99, 95%CI: 0.006 1.947), had a relative or friend who had contracted COVID-19 (β= 1.825, 95%CI: 0.122 3.528), and had poor health (β= 4.867, 95%CI: 0.379 9.354) had higher PCL-5 scores, while the population aged over 60 years (β= -3.3, 95%CI: -5.278 -1.245), who agreed that COVID-19 information was released in a timely manner (β=-9.803, 95%CI: -10.893 -8.713), who had experienced a relatively limited impact of COVID-19 on their life (β= -2.053, 95%CI: -3.394 -0.712), and who agreed that the local prevention initiatives were sophisticated (β=-4.851, 95%CI: -9.533 -0.168) had lower PTSD scores. Conclusions: Outbreaks of acute infectious diseases can have long-term psychological health effects in the general population. In addition, health policy makers need to be concerned about and implement measures to support the mental health of vulnerable groups.